Implementasi Huffman Kompresi Pada Steganografi Ruang HSV - Dio Aldino Bugis (SEMINAR NASIONAL TEKNOLOGI INFORMASI & KOMUNIKASI, 2021)
Sending a message or confidential data that is very important requires a high level of security. however, threats can still occur from irresponsible parties. Data security can be done using cryptography and steganography simultaneously in the image space. So it will be difficult to realize that in an image there is a secret message in the form of stored text. Steganography means the science and art of hiding secret messages in other messages so that the existence of these secret messages cannot be known. By using the Huffman compression algorithm, we can insert a message in an image without changing the original form of the message. The Huffman algorithm is a compression algorithm that is quite old but is still evaluated as a reliable data compression algorithm. Huffman algorithm is a compression technique that uses bits to represent character data. In general, this algorithm can provide savings of as much as 20%-30%. The application of the Steganography and Huffman Compression algorithms that have been carried out can be combined well. The implementation of the two methods resulted in a method that can deliver a better level of security.